Neoadjuvant immunotherapy across cancers: meeting report from the Immunotherapy Bridge—December 1st–2nd, 2021 - Elizabeth M. Burton; Rodabe N. Amaria; Tina Cascone; Myriam Chalabi; Neil D. Gross; Elizabeth A. Mittendorf; Richard A. Scolyer; Padmanee Sharma; Paolo A. Ascierto (Journal of Translational Medicine, 2022)
Abstract After the success of immunotherapy in the treatment of advanced metastatic cancer, further evaluation in earlier settings, including high-risk, surgically-resectable disease is underway. Potential benefits of a neoadjuvant immunotherapeutic approach include presurgical tumor shrinkage, reduced surgical morbidity, early eradication of micrometastases and prevention of distant disease, and greater antigen-specific T cell response. For some cancers, pathologic response has been established as a surrogate measure for long-term outcomes, therefore offering the ability for early and objective assessment of treatment efficacy and the potential to inform and personalize adjuvant treatment clinical decision-making. Leveraging the neoadjuvant treatment setting offers the ability to deeply interrogate longitudinal tissue in order to gain translatable, pan-malignancy insights into response and mechanisms of resistance to immunotherapy. Neoadjuvant immunotherapy across cancers was a focus of discussion at the virtual Immunotherapy Bridge meeting (December 1–2, 2021). Clinical, biomarker, and pathologic insights from prostate, breast, colon, and non-small-cell lung cancers, melanoma and non-melanoma skin cancers were discussed and are summarized in this report.